Produção e purificação de enzima catalase recombinante - Martins-Meira, Josuelen de Paula (2022)
Enzymes are biocatalysts, predominantly of protein origin, responsible for most of the reactions in living microorganisms, thus, they are agents that accelerate the speed of reactions in a highly efficient way and with low energy consumption. Due to such characteristics, enzymes have become increasingly interesting in the most diverse industrial branches, with catalase being a major highlight and of high technological interest. This enzyme can be applied in different sectors such as the paper, food, textile, pharmaceutical and dental industries. However, obtaining it has certain limitations due to the high cost of production. In this context, one of the alternatives for obtaining these enzymes for industrial application is through recombinant expression, since they are less complicated to maintain in the laboratory and present high levels of activity. Catalase from Serratia marcescens presents itself in an interesting way, being an enzyme that works in a wide range of pH and exhibits high stability in natural media, in addition to presenting high activity in acidic conditions (pH between 4.4 and 6.6) and low temperatures, from 6° to 15°C. This work has as main objective the heterologous production of Serratia marcescens catalase protein in recombinant Escherichia coli (Rosetta Gami pLysS) cells, as well as the purification of the protein and deteccion of its activity. Catalase expression was performed within 4 hours after induction with 0.4 mM IPTG at 37 °C and, subsequently, the protein was purified using the nickel resin affinity chromatography technique. The expression and purification analyzes were observed in polyacrylamide gel (SDS-PAGE 12%) and the determination of enzymatic activity was observed by verifying the production of molecular oxygen from the degradation of hydrogen peroxide by the enzyme catalase.